2020
DOI: 10.1037/rmh0000127
|View full text |Cite
|
Sign up to set email alerts
|

Clinician telehealth attitudes in a rural community mental health center setting.

Abstract: Telehealth-based services in community mental health settings are on the rise and growth is expected to continue. Negative clinician attitudes toward telehealth have been identified as a key barrier to overall telehealth acceptance and implementation. The present study examined rural clinical mental health staff members' attitudes toward telehealth. One hundred clinicians participated in a mixed-methods, Internet-based survey. Eighty-nine percent of respondents reported a favorable or neutral opinion of telehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 24 publications
2
52
2
Order By: Relevance
“…A more recent study [ 74 ] captured a range of psychologists’ concerns about the possibility of creating and/or maintaining TA by VC. Another study on parental counseling [ 75 ] claimed the overall satisfaction of clinicians and clients.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study [ 74 ] captured a range of psychologists’ concerns about the possibility of creating and/or maintaining TA by VC. Another study on parental counseling [ 75 ] claimed the overall satisfaction of clinicians and clients.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have examined the use of telehealth in various clinical capacities and settings, including in rural communities (McClellan et al, 2020), in the context of supervision (Jordan & Shearer, 2019), among veterans with mental health concerns (Abel et al, 2018), among justice-involved individuals (Batastini et al, 2016), and in psychiatric emergency settings (Freeman et al, 2020). Telehealth also appears to be a less expensive alternative to in-person psychiatric services (Serhal et al, 2019).…”
Section: What Is Telehealth Videoconferencing?mentioning
confidence: 99%
“…Existing qualitative studies tend to focus on understanding the experiences of a single group, such as patients, psychiatrists or allied healthcare providers (i.e. therapists and nurses) [8][9][10][11][12][13]. As for the use of TMH in the Indigenous Canadian context, researchers have found that cultural rapport can be built, albeit with some difficulty [14,15].…”
Section: Introductionmentioning
confidence: 99%